Self-Regulation in Primary School - García Gaitero, Óscar (Rastros Rostros, 2014)
Most research studies on self-regulated learning have been conducted with students in secondary and higher education, forgetting that primary school students are the ones who may face the most problems when cognitive and metacognitive strategies are applied. This article highlights the importance of training children how to self-regulate their learning as they start their studies. In these first crucial years, students learn and develop attitudes of self-sufficiency that are easier to change than when they have already developed and consolidated learning styles